Potensi Pasar dan Kelayakan Ekonomi Briqball: Inovasi Briket Ramah Lingkungan Berbahan Dasar Limbah Tempurung Kelapa dan Ampas Tebu - Salsabila; Rezi Widyan Ananta; Rozan Satyo Hakim; Deviana Sevitra; Maudila Isnaini; Aditya Zikri Syahputra (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2024)
The availability of alternative energy sources in Indonesia is diverse, one of which is biomass derived from organic waste. With the increasing demand for fuel each year, innovative solutions are needed to address the limitations of energy sources. Briqball emerges as an eco-friendly briquette product utilizing coconut shell charcoal residue and sugarcane bagasse. This study aims to analyze the market potential and economic feasibility of Briqball as an efficient and environmentally friendly fuel alternative. The data analysis methods used in this study include calculations of costs, revenue, profit, BEP, R/C Ratio, B/C Ratio, and ROI. Based on the data analysis, it was found that the Briqball business or the briquette innovation made from coconut shell charcoal residue and sugarcane bagasse is profitable, with a total monthly profit of IDR 2,021,667. The calculation results show a production BEP of 94.4 kg, a price BEP of IDR 1,228.3/kg, an R/C ratio of 2.6, a B/C ratio of 1.64, and an ROI of 21,9%. Therefore, it can be concluded that the Briqball business is feasible and viable.